2019
DOI: 10.1371/journal.pcbi.1007185
|View full text |Cite
|
Sign up to set email alerts
|

Assessing key decisions for transcriptomic data integration in biochemical networks

Abstract: To gain insights into complex biological processes, genome-scale data (e.g., RNA-Seq) are often overlaid on biochemical networks. However, many networks do not have a one-to-one relationship between genes and network edges, due to the existence of isozymes and protein complexes. Therefore, decisions must be made on how to overlay data onto networks. For example, for metabolic networks, these decisions include (1) how to integrate gene expression levels using gene-protein-reaction rules, (2) the approach used f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(116 citation statements)
references
References 33 publications
2
114
0
Order By: Relevance
“…Doing so, they also found metabolic housekeeping functions shared across all tissues and showed similarities between metabolic activities across tissues in the same organ systems. Unfortunately, the construction and analysis of such computational models is a complex and difficult task requiring expert knowledge of the tissues and modeling framework 19,20,48 . To overcome this problem, our framework successfully combines the capacity to provide mechanistic insights of network based approaches and the simplicity of enrichment analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doing so, they also found metabolic housekeeping functions shared across all tissues and showed similarities between metabolic activities across tissues in the same organ systems. Unfortunately, the construction and analysis of such computational models is a complex and difficult task requiring expert knowledge of the tissues and modeling framework 19,20,48 . To overcome this problem, our framework successfully combines the capacity to provide mechanistic insights of network based approaches and the simplicity of enrichment analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The gene score for each reaction is selected by taking the minimum expression value amongst all the genes associated to an enzyme complex (AND rule) and the maximum expression value amongst all the genes associated to an isozyme (OR rule) 53 . Note that we have recently benchmarked the influence of preprocessing methods on the definition of the set of active genes and observed that this parameter combination presented the best performance 20 .…”
Section: Preprocessing Of Gene Expression Datamentioning
confidence: 99%
“…For preprocessing one applies a threshold to the transcriptomics dataset at a gene-or enzyme-level to decide if the gene or enzyme is expressed to sufficient levels to be considered active. Previous work identified thresholding as the most influential parameter impacting model content in context-specific models (Opdam et al, 2017;Richelle, Joshi, et al, 2018). However, it remains unclear how such thresholds be decided.…”
Section: Discussionmentioning
confidence: 99%
“…cancer cell lines, tissues, etc.). For existing thresholding methods (Richelle, Joshi, et al, 2018) to accurately capture cellular states, they must be able to select housekeeping reactions, i.e. reactions associated with housekeeping genes.…”
Section: Existing Thresholding Methods Remove Many Housekeeping Reactmentioning
confidence: 99%
See 1 more Smart Citation